EVALUASI PENERAPAN PERNYATAAN STANDAR AKUNTANSI PEMERINTAH (PSAP) No. 07 TAHUN 2010 TENTANG ASET TETAP DI KANTOR DESA PANYIPATAN - Ines Saraswati Machfiroh Machfiroh; Rahmi Nadiar; Nor Rahma Rizka; Saudah (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2026)
This research is motivated by problems in the management of fixed assets at the Panyipatan Village Office, especially regarding asset depreciation, which is still based on observations of physical conditions and has not yet used the straight-line method as recommended by government accounting standards. The purpose of this research is to evaluate the extent to which the implementation of PSAP No. 07 of 2010 is carried out in the management of village fixed assets. The approach used in this research is a qualitative method with interview and documentation techniques. The research focus includes the processes of classification, measurement, depreciation, and disposal of fixed assets in accordance with the provisions of PSAP No. 07. The results show that the management of assets such as buildings, equipment, and machinery has generally followed the standards, including in terms of recording and recognition of assets based on acquisition value. However, there are still shortcomings in the application of depreciation methods and systematic asset recording. Therefore, an improvement in the technical capabilities of village officials is needed so that asset management becomes more accurate, transparent, and in accordance with applicable standards.